Computer chess move-ordering schemes using move influence. - Kieran Greer (Artificial intelligence.)
The chessmaps heuristic is a pattern-oriented approach to previous termordering movesnext term for the game of previous termchess.next term It uses a neural network to learn a relation between the control of the squares and the previous terminfluencenext term of a previous termmove.next term Depending on what squares a player controls, the chessmaps heuristic tries to determine where the important areas of the chessboard are. previous termMoves that influencenext term these important areas are then ordered first. The heuristic has been incorporated into a previous termmove-orderingnext term algorithm that also takes account of immediate tactical threats. Human players also rely strongly on patterns when selecting previous termmoves,next term but would also consider immediate tactical threats, so this previous termmove-orderingnext term algorithm is an attempt to mimic something of the human thought process when selecting a previous termmove.next term This paper presents a new definition for the previous terminfluencenext term of a previous termmove,next term which improves the performance of the heuristic. It also presents a new experience-based approach to determining what areas of the chessboard are important, which may actually be preferred to the chessmaps heuristic. The results from game-tree searches suggest that the previous termmove-orderingnext term algorithm could compete with the current best alternative of using the history heuristic with capture previous termmovesnext term in a brute-force search.